Low self-control, perceived social support and internet gaming addiction: findings from an ethnicity minority region in China - Meng, Cui; Quancai, Li; Kunjie, Cui; Yanyu, Xin; Wencai, Lama; Yiwei, Xia (Frontiers in Psychiatry, 2024)
Background Adolescent Internet gaming addiction (IGA) is an pincreasing global concern. Drawing on self-control theory, social support theory, and problem behavior theory, this study aimed to examine the relationships between low self-control, perceived social support, and IGA among Chinese Yi and Non-Yi adolescents, with a focus on the moderating role of perceived social support and ethnic differences. Methods A cross-sectional study was conducted among 1,997 adolescents (53.78% female, mean age 14.70 years) in Liangshan Yi Autonomous Prefecture, Sichuan Province, China, using a multi-stage cluster random sampling method. Participants completed questionnaires assessing IGA (Internet Gaming Disorder Scale-Short Form), low self-control (Low Self-Control Scale), and perceived social support (Multidimensional Scale of Perceived Social Support). Data were analyzed using descriptive statistics, t-tests, OLS regression, and the seemingly unrelated estimator (SUE). Results Low self-control was positively associated with IGA (β = 0.35, p < 0.001), while perceived social support was negatively associated with IGA (β = -0.27, p < 0.001). Perceived social support, particularly from family (β = -0.43, p < 0.05) and significant others (β = -0.49, p < 0.01), moderated the relationship between low self-control and IGA. These associations were more salient among Yi adolescents compared to non-Yi adolescents. Conclusions This study highlights the protective role of perceived social support, especially from family and significant others, in buffering the risk of low self-control on IGA. The findings extend self-control theory and social support theory, and provide empirical support for problem behavior theory in a cross-cultural context. The results underscore the importance of considering cultural contexts in understanding IGA and developing targeted interventions for ethnic minority adolescents.